MANAGEMENT OF CUTANEOUS PAPILLOMA IN AN ONGOLE (BOS INDICUS) CALF - S.P. Kurati; N.R. Srikanth; M.P. Kumar; M. Mutha Rao (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A female Ongole calf aged one year and nine months was found to have nodular development around the left eye and neck region. Clinical examination revealed that the calf had cutaneous papilloma (wart), which was treated with autohemotherapy, ivermectin and levamisole injections along with placement of a ligature around wart’s base. On the third day of treatment, a large papilloma on the left lower eyelid dried up and sloughed off. On the tenth day of therapy, the warts on the upper eyelid and neck began to dry and flake off, leaving behind barely visible scars at the original growth sites. The animal underwent an uncomplicated recovery and completely recovered from the ailment.